Amino-functionalized MOF gel cross-linked polyimide helium separation membrane and preparation method thereof

By introducing amino groups on the surface of amino-functionalized MOF gel and chemically crosslinking with polyimide, the problem of insufficient performance of existing helium separation membrane materials is solved, and efficient and stable helium separation performance and mechanical stability are achieved.

CN119746651APending Publication Date: 2025-04-04HUNAN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510044823.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the existing helium separation technology, the separation performance of membrane separation materials is limited, making it difficult to take into account both high permeability and high selectivity, and the hybrid matrix membrane has problems of interface defects and insufficient stability.

Method used

By introducing amino groups (-NH2) on the surface of the aminofunctionalized metal organic frame (MOF) gel, chemically crosslinking with polyimide (PI) is formed to form a stable imide bond structure, improving the interface compatibility and dispersion between the MOF material and the matrix, and optimizing the microporous structure and gas separation path of the membrane.

Benefits of technology

It significantly improves the selectivity and permeability of helium, enhances the mechanical strength and long-term stability of the membrane, overcomes the interfacial defects and insufficient stability of traditional hybrid matrix membranes, and is suitable for helium separation under complex conditions such as high temperature and high pressure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746651A_ABST
    Figure CN119746651A_ABST
Patent Text Reader

Abstract

The invention relates to an amino-functionalized MOF gel (MOF gel) and polyimide (PI-T) cross-linked mixed matrix membrane (MMMs) as well as a preparation method and application thereof. Amino groups (-NH2) are introduced to the surface of MOF gel and chemically cross-linked with dianhydride groups in PI-T to generate a stable imide bond structure, so that the interfacial compatibility and dispersity of the filler and a matrix are remarkably enhanced. Experiments show that the ZIF-67-NH2gel-coated PI-T membrane forms a complete membrane under the high filling amount (38wt%), the He permeability coefficient is 480 + / -16.4 Barrer, the He / CH4 selectivity reaches 110.3 + / -5.6, and the unfunctionalized ZIF-67 gel is broken due to insufficient interface bonding force under the high filling amount. Compared with a ZIF-67 gel membrane, the He / CH4 selectivity (94.7 + / -0.5) of the ZIF-67-NH2NH2Gel membrane is far higher than that of a ZIF-67 gel membrane (16.1 + / -0.8) under the filling amount of 31 wt%. The problems of interface defects and insufficient stability of a traditional mixed matrix membrane are solved, efficient helium separation is achieved, the method is simple and convenient, the method is suitable for large-scale production, and a solution is provided for industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of membrane separation, and in particular to a mixed matrix membrane prepared by amino-functionalized metal organic framework (MOF) gel cross-linked polyimide and a method for using the mixed matrix membrane in He separation. Background Art

[0002] Helium is an important non-renewable strategic resource, which is widely used in fields such as nuclear magnetic resonance imaging, low-temperature superconductivity, aerospace and semiconductor industry. However, the reserves of helium on the earth are extremely limited, mainly from associated helium in natural gas. Due to the generally low helium content in natural gas in my country, the extraction of helium faces high economic costs and technical difficulties. At present, my country's annual demand for helium is about 22 million cubic meters, but domestic production capacity is extremely limited, and import dependence exceeds 95%. How to efficiently and economically extract helium from helium-poor natural gas has become a scientific and engineering problem that needs to be solved urgently. At present, the main technologies used for helium separation in industry include cryogenic separation, adsorption separation and membrane separation. Cryogenic separation relies on the difference in boiling points of gases and achieves separation through low-temperature liquefaction. Although the separation efficiency is high, the equipment is complex, the energy consumption is high and the cost is expensive; adsorption separation uses the selective adsorption ability of adsorbents to achieve separation, but the efficiency is limited in the separation of low-concentration helium, and the regeneration process of adsorbents is complicated. In contrast, membrane separation technology has become a preferred technology with its advantages of low energy consumption, simple equipment and continuous operation. However, the separation performance of existing membrane materials is still limited, and it is difficult to achieve both high permeability and high selectivity at the same time, and cannot fully meet the needs of industrial applications.

[0003] The membrane materials currently used for helium separation mainly include polymer membranes, metal organic framework membranes (MOF membranes) and mixed matrix membranes (MMMs). Polymer membranes are widely used due to their good processability and excellent mechanical properties, but they are limited by the "permeability and selectivity trade-off effect" and it is difficult to break through the performance bottleneck; MOF membranes show potential in gas separation due to their high porosity and adjustable pore size, but their mechanical properties are poor and the film formation is difficult, which limits their practical application. Mixed matrix membranes introduce MOF materials into polymer matrices, combining the advantages of both, and have become a hot topic in helium separation research. However, due to the poor interface compatibility between MOF materials and polymer matrices, interface pore defects are easily formed, leading to gas leakage; in addition, the poor dispersibility and stability of MOF in polymers further limit the improvement of the separation performance of mixed matrix membranes.

[0004] In order to overcome the interface defects and stability problems of mixed matrix membranes, researchers have made some progress in recent years by surface functionalizing MOF materials (such as introducing carboxyl, amino or hydroxyl groups) to enhance their interfacial bonding with polymer matrices. However, most functionalized MOFs are limited to physical surface modification and it is difficult to form a stable chemical cross-linked structure. At the same time, the functionalization process often leads to a decrease in the porosity and specific surface area of ​​the MOF material, weakening its contribution to gas separation performance. To solve the above problems, the present invention proposes a mixed matrix membrane based on amino-functionalized MOF gel (MOF gel) and polyimide (PI) cross-linking. By introducing amino groups (-NH2) on the surface of MOF gel, it undergoes a chemical cross-linking reaction with the dianhydride groups in PI to generate stable imide bonds, which not only significantly improves the dispersibility and interfacial compatibility of MOF materials in the matrix, but also optimizes the microscopic pore structure and gas diffusion path of the membrane, thereby achieving efficient separation of helium. The present invention provides a mixed matrix membrane with excellent performance, which provides a new solution for the industrial application of helium separation technology. Summary of the invention

[0005] The object of the present invention is to provide a MOF-NH2 gel@PI MMMs, which has high He separation performance and a simple preparation method and is suitable for large-scale production.

[0006] To achieve the above object, the specific technical solutions of the present invention are as follows:

[0007] Step (1): Disperse the amino MOF gel into the solution and ultrasonicate for 30 minutes to make it evenly dispersed.

[0008] Step (2): Weigh an appropriate amount of polyimide (PI), add it to the solvent and stir it at room temperature for 24 hours to completely dissolve the PI to obtain a uniform and transparent PI solution. Then, filter the solution to remove impurities and set it aside.

[0009] Step (3): slowly add the PI solution prepared in step (2) to the amino MOF Gel dispersion in step (1) by dropwise addition, stir at room temperature for 24 hours, and then ultrasonically treat for 30 minutes to ensure that a uniform casting film mixed solution is formed.

[0010] Step (4): Slowly pour the mixed solution prepared in step (3) into a flat glass petri dish, dry it naturally at 120°C for 12 hours (without blowing), and then vacuum dry it at 150°C for 12 hours. After cooling to room temperature, carefully peel off the membrane to obtain the final amino MOF gel@PI mixed matrix membrane (MMMs).

[0011] In step (1) of the present invention, the amino MOF gel can be selected from amino ZIF-8 gel (ZIF-8-NH2 gel), amino ZIF-67 gel (ZIF-67-NH2 gel) or amino UIO-66 gel (UIO-66NH2 gel).

[0012] In steps (1) and (2) of the present invention, the solution is the same solution, N,N-dimethylformamide (DMF) or N-methylpyrrolidone (NMP).

[0013] In step (2) of the present invention, the polyimide can be selected from 6FDA-TMPD (PI-T), BPDA-FDA-6FAP (PI-B), PMDA-MDA (P84), Ultem, BTDA-MDA (Matrimid), etc.

[0014] In step (3) of the present invention, the content of the amino MOF gel is 1 to 40 wt % of the mass of the amino MOF gel@PI MMMs.

[0015] In step (3) of the present invention, the total mass concentration of PI and amino MOF gel in the mixed solution for film casting is 1.5-3.0 wt%.

[0016] According to one aspect of the present invention, there is provided a use of the amino MOF gel@PI MMMs in gas separation.

[0017] Optionally, the amino MOF gel@PI MMMs is used in the separation of a mixture containing He.

[0018] Preferably, the gas comprises at least one of N2 and CH4.

[0019] In the present application, the gas mixture contacts one side of the amino-MOF gel@PI MMMs, thereby introducing He to permeate the amino-MOF gel@PI MMMs to achieve a gas separation effect.

[0020] Compared with the prior art, the present invention has the following beneficial technical effects:

[0021] The present invention achieves chemical crosslinking of MOF and polyimide (PI) matrix by introducing amino groups (-NH2) on the surface of MOF gel, generating a stable imide bond structure, significantly enhancing the interfacial compatibility between MOF material and matrix, and effectively overcoming the common interfacial defects and insufficient stability problems in traditional mixed matrix membranes. At the same time, the present invention optimizes the microscopic pore structure and gas separation path of the membrane, maintains the high porosity and specific surface area of ​​the MOF material, and significantly improves the selectivity and permeability of helium. The dense network structure formed by chemical crosslinking greatly improves the mechanical strength and long-term stability of the membrane, making it perform well under complex conditions such as high temperature and high pressure.

[0022] The membrane preparation method provided by the invention is easy to operate and suitable for large-scale production, and provides an economical, efficient and high-performance solution for the industrial application of helium separation technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 2. XRD patterns of ZIF-67-NH2 gel / PI-T MMMs in Example 1 and Comparative Example 1.

[0024] Figure 2 2. The TGA graphs of ZIF-67-NH2 gel / PI-T MMMs in Example 4 and Comparative Example 1.

[0025] Figure 3 The DSC graphs of ZIF-67-NH2 gel / PI-T MMMs in Example 4 and Comparative Example 1.

[0026] Figure 4 FT-IR graph of ZIF-67-NH2 gel / PI-T MMMs in Examples 1-4 and Comparative Example 1.

[0027] Figure 5 FT-IR local enlargement (1680-1750cm) of ZIF-67-NH2 gel / PI-T MMMs in Examples 1-4 and Comparative Example 1 -1 )picture.

[0028] Figure 6 FT-IR local enlargement (700-800cm) of ZIF-67-NH2 gel / PI-T MMMs in Examples 1-4 and Comparative Example 1 -1 )picture.

[0029] Figure 7 2 are N2 adsorption diagrams of the membranes prepared in Example 4 and Comparative Example 1.

[0030] Figure 8 The pore size distribution diagram of the membranes prepared in Example 4 and Comparative Example 1 is shown.

[0031] Fig. 9 The mesopore size distribution diagram of the membranes prepared in Example 4 and Comparative Example 1.

[0032] Fig.10 This is a diagram of Example 4 and Comparative Examples 1 and 4 being immersed in DMF solution.

[0033] Fig.11 This is a graph showing the helium separation performance of the membranes prepared in Examples 1-4 and Comparative Example 1.

[0034] Fig.12 This is a graph showing the helium separation performance of the membranes prepared in Comparative Examples 1-4.

[0035] Fig.13 The helium separation performance and upper bound comparison of the membranes prepared in Examples 1-4 and Comparative Examples 1-4 are shown in FIG.

[0036] Fig.14 This is the helium separation performance of the membrane prepared in Example 4 under the conditions of simulated industrial feed gas temperature swing.

[0037] Fig.15 This is the helium separation performance of the membrane prepared in Example 4 under the pressure swing conditions simulating industrial feed gas.

[0038] Fig.16 This is the long-term stability of the helium separation performance of the membrane prepared in Example 4 under simulated industrial feed gas conditions. DETAILED DESCRIPTION

[0039] The technical solution of the present invention is further described below through several specific embodiments, but the present application is not limited thereto. Without departing from the content and scope of the present invention, any changes and implementations should be included in the technical scope of the present invention.

[0040] Example 1:

[0041] Step (1): 0.015 g ZIF-67-NH2 gel was dispersed in DMF and ultrasonicated for 30 minutes to make it evenly dispersed.

[0042] Step (2): Weigh 0.15 g of PI-T, add it into DMF and stir it at room temperature for 24 hours to completely dissolve PI to obtain a uniform and transparent PI solution. Then, filter the solution to remove impurities and set aside.

[0043] Step (3): Slowly add the PI-T solution prepared in step (2) to the ZIF-67-NH2gel solution in step (1) by dropwise addition, stir at room temperature for 24 hours, and then ultrasonically treat for 30 minutes to ensure the formation of a uniform casting film mixed solution.

[0044] Step (4): The mixed solution prepared in step (3) was slowly poured into a flat glass petri dish, dried naturally at 120°C for 12 hours (without blowing), and then vacuum dried at 150°C for 12 hours. After cooling to room temperature, the membrane was carefully peeled off to obtain the final 13wt% ZIF-67-NH2 gel@PI-T MMMs.

[0045] Example 2:

[0046] Step (1): 0.030 g ZIF-67-NH2 gel was dispersed in DMF and ultrasonicated for 30 minutes to make it evenly dispersed.

[0047] Steps (2)-(3) are the same as in Example 1

[0048] Step (4): The mixed solution prepared in step (3) was slowly poured into a flat glass petri dish, dried naturally at 120°C for 12 hours (without blowing), and then vacuum dried at 150°C for 12 hours. After cooling to room temperature, the membrane was carefully peeled off to obtain the final 23wt% ZIF-67-NH2 gel@PI-T MMMs.

[0049] Example 3:

[0050] Step (1): 0.045 g ZIF-67-NH2 gel was dispersed in DMF and ultrasonicated for 30 minutes to make it evenly dispersed.

[0051] Steps (2)-(3) are the same as in Example 1

[0052] Step (4): The mixed solution prepared in step (3) was slowly poured into a flat glass petri dish, dried naturally at 120°C for 12 hours (without blowing), and then vacuum dried at 150°C for 12 hours. After cooling to room temperature, the membrane was carefully peeled off to obtain the final 31wt% ZIF-67-NH2 gel@PI-T MMMs.

[0053] Example 4:

[0054] Step (1): 0.060 g ZIF-67-NH2 gel was dispersed in DMF and ultrasonicated for 30 minutes to make it evenly dispersed.

[0055] Steps (2)-(3) are the same as in Example 1

[0056] Step (4): The mixed solution prepared in step (3) was slowly poured into a flat glass petri dish, dried naturally at 120°C for 12 hours (without blowing), and then vacuum dried at 150°C for 12 hours. After cooling to room temperature, the membrane was carefully peeled off to obtain the final 38wt% ZIF-67-NH2 gel@PI-T MMMs.

[0057] Comparative Example 1:

[0058] Step (1): 0.15 g of PI-T was dissolved in DMF, added to DMF and stirred at room temperature for 24 hours to completely dissolve PI to obtain a uniform and transparent PI solution. Subsequently, the solution was filtered to remove impurities and set aside.

[0059] Step (2): slowly pour the mixed solution prepared in step (1) into a flat glass petri dish, dry it naturally at 120°C for 12 hours (without blowing), and then vacuum dry it at 150°C for 12 hours. After cooling to room temperature, carefully peel off the film to obtain the final PI-T.

[0060] Comparative Example 2:

[0061] Step (1): 0.015 g ZIF-67 gel was dispersed in DMF and ultrasonicated for 30 minutes to make it evenly dispersed.

[0062] Steps (2)-(3) are the same as in Example 1

[0063] Step (4): The mixed solution prepared in step (3) was slowly poured into a flat glass petri dish, and dried naturally at 120°C for 12 hours (without blowing), and then vacuum dried at 150°C for 12 hours. After cooling to room temperature, the membrane was carefully peeled off to obtain the final 13wt% ZIF-67gel / PI-T MMMs.

[0064] Comparative Example 3:

[0065] Step (1): 0.030 g ZIF-67 gel was dispersed in DMF and ultrasonicated for 30 minutes to make it evenly dispersed.

[0066] Steps (2)-(3) are the same as in Example 1

[0067] Step (4): The mixed solution prepared in step (3) was slowly poured into a flat glass petri dish, dried naturally at 120°C for 12 hours (without blowing), and then vacuum dried at 150°C for 12 hours. After cooling to room temperature, the membrane was carefully peeled off to obtain the final 23wt% ZIF-67gel / PI-T MMMs.

[0068] Comparative Example 4:

[0069] Step (1): 0.045 g ZIF-67 gel was dispersed in DMF and ultrasonicated for 30 minutes to make it evenly dispersed.

[0070] Steps (2)-(3) are the same as in Example 1

[0071] Step (4): The mixed solution prepared in step (3) was slowly poured into a flat glass petri dish, and dried naturally at 120°C for 12 hours (without blowing), and then vacuum dried at 150°C for 12 hours. After cooling to room temperature, the membrane was carefully peeled off to obtain the final 13wt% ZIF-67gel / PI-T MMMs.

[0072] The He permeability and selectivity of the MMMs in Examples 1-4 and Comparative Examples 1-4 at 0.3 MPa and 35°C and when the gas mixture is He / CH4 are shown in Table 1. Table 1

[0073] The experimental results show that at 31wt% filler content, the He permeability coefficient of ZIF-67gel / PI-T membrane (1107±31.7Barrer) is significantly higher than that of ZIF-67-NH2 gel / PI-T membrane (426±12.8Barrer), but its He / CH4 selectivity (16.1±0.8) is much lower than that of ZIF-67-NH2 gel@PI-T membrane (94.7±0.5). This phenomenon reveals the significant difference in membrane performance and stability between unfunctionalized ZIF-67gel and amino-functionalized ZIF-67gel, and also reflects the profound influence of filler interfacial compatibility on membrane performance. For unfunctionalized ZIF-67gel, although its higher porosity and specific surface area significantly improve the permeability of helium, due to the weak interaction between it and the polyimide (PI-T) matrix, the filler is prone to agglomeration in the matrix, resulting in the formation of non-selective gas transmission channels at the interface. These interfacial defects not only significantly reduce the He / CH4 selectivity, but also limit the further increase of the filler content. When the filler content reaches 38wt%, the ZIF-67gel / PI-T membrane cannot form a complete membrane due to insufficient interfacial bonding and uneven stress distribution, but splits into small fragments, completely losing the continuity and separation function of the membrane. In contrast, ZIF-67-NH2 gel significantly improves the interfacial compatibility with the PI-T matrix by introducing amino groups (-NH2) on the surface, and generates stable imide bonds through chemical cross-linking reactions with the dianhydride groups in PI-T. The chemical cross-linking effect not only improves the dispersion of the filler in the matrix, but also effectively enhances the mechanical strength and overall stability of the membrane. At a filler content of 38wt%, the ZIF-67-NH2 gel / PI-T membrane can still maintain a complete membrane structure and exhibit excellent separation performance. The He permeability coefficient is 480±16.4Barrer, and the He / CH4 selectivity is further improved to 110.3±5.6. This result shows that amino functionalization and chemical cross-linking play a key role in improving the stability and performance uniformity of the membrane. In summary, the interface compatibility of ZIF-67gel and PI-T matrix is ​​poor, which makes it difficult to form a complete membrane at a high filling content. ZIF-67-NH2 gel achieves a stronger interface bonding with the matrix through surface functionalization, overcoming the problem of easy rupture of the membrane at a high filling content. At the same time, the ZIF-67-NH2 gel@PI-T membrane significantly optimizes the balance between permeability and selectivity, so that it still maintains excellent separation performance and mechanical stability at a high filler content. This study shows that the interface functionalization and chemical cross-linking of fillers are effective strategies for the development of high-performance mixed matrix membranes, providing an important solution for the industrial application of efficient helium separation technology.

[0074] The above are only several embodiments of the present invention and are not intended to limit the present invention in any form. Although the present invention is disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, using the above disclosed technical content to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A helium separation membrane of amino-functional MOF gel (MOF gel) cross-linked polyimide (PI) and a preparation method thereof, characterized in that: The amino MOF gel@PI MMMs comprises a PI matrix and an amino MOF gel; The amino MOF gel refers to a MOF gel with amino functional groups (-NH2) on the surface of the MOF gel; The PI refers to a polymer material prepared by polycondensation of dianhydride and diamine, and is used as a base material for mixed matrix membranes.

2. The amino MOF gel@PI MMMs according to claim 1, characterized in that: The amino MOF gel can be amino ZIF-8 gel (ZIF-8-NH2 gel), amino ZIF-67 gel (ZIF-67-NH2 gel) or amino UIO-66 gel (UIO-66NH2 gel).

3. The amino MOF gel@PI MMMs according to claim 1, characterized in that: The content of the amino MOF gel is 1 wt % to 40 wt % of the mass of the amino MOF gel@PI MMMs.

4. The amino MOF gel@PI MMMs according to claim 1, characterized in that: The PI can be selected from at least one of 6FDA-TMPD (PI-T), BPDA-FDA-6FAP (PI-B), PMDA-MDA (P84), Ultem, and BTDA-MDA (Matrimid).

5. A method for preparing the amino MOF gel@PI MMMs according to any one of claims 1 to 4, characterized in that: The amino MOF gel@PI MMMs are obtained by forming a mixed film solution containing PI and amino MOF gel into a film and subjecting the film to vacuum treatment.

6. The preparation method according to claim 5, characterized in that: The film casting mixed solution is obtained by mixing the polymer-containing solution a with the amino-containing MOFgel solution b.

7. The preparation method according to claim 5, characterized in that: In the mixed solution for casting the membrane, the total mass concentration of the polymer and the IL@MOF gel is 1.5-3wt%; Preferably, the solvent of the film casting mixed solution is selected from one of N,N-dimethylformamide (DMF) and N-methylpyrrolidone (NMP).

8. Use of the IL@MOF gel MMMs according to any one of claims 1 to 4 or the amino MOF gel@PI MMMs prepared by the preparation method according to any one of claims 5 to 7 in gas separation.

9. The use according to claim 8, characterized in that: Application of the amino MOF gel@PI MMMs in separation of He-containing gas mixtures; Preferably, the gas comprises at least one of N2 and CH4.

Citation Information

Patent Citations

  • Metal organic framework gel mixed matrix membrane as well as preparation method and application thereof

    CN117443208A